2013
DOI: 10.1103/physrevc.87.064604
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear temperatures from evaporation fragment spectra and observed anomalies

Abstract: Abstract. The extreme back-angle evaporation spectra of alpha, lithium, beryllium, boron and carbon from different compound nuclei near A ≈100 (E X = 76 -210 MeV) have been compared with the predictions of standard statistical model codes such as 'CASCADE' and 'GEMINI'. It was found that the shapes of the alpha spectra agree well with the predictions of the statistical models. However the spectra of lithium, beryllium, boron and carbon show significantly gentler slopes implying higher temperature of the residu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The equilibrium temperature mostly lies in the range of 1,5 -6 MeV with the median value being 3,5 MeV. This result is in agreement with measurements conducted in various ways[16]. This gives us one more evidence that our model separates different reaction stages well.Using the model we also calculated partial yields and contributions of differentstages into the full yields of p, d t. The A-dependence of evaporation yields of protons is presented in the fig.…”
supporting
confidence: 91%
“…The equilibrium temperature mostly lies in the range of 1,5 -6 MeV with the median value being 3,5 MeV. This result is in agreement with measurements conducted in various ways[16]. This gives us one more evidence that our model separates different reaction stages well.Using the model we also calculated partial yields and contributions of differentstages into the full yields of p, d t. The A-dependence of evaporation yields of protons is presented in the fig.…”
supporting
confidence: 91%
“…This equation just defines a surface-evaporation function (similar to surface evaporation of liquids and its Maxwellian distribution function), where N, E b , and T are the normalization constant, emission barrier, and temperature (slope of high energy side of the evaporated spectra) respectively. Thus, it is shown that the nuclear temperature T of an ensemble of the residual nuclei (including evaporated particles and the residual nucleus) can be obtained from the slope of the exponential tail of energy spectra of the evaporated particles [62]:…”
Section: Statistical Mechanism Of Nuclear Evaporationmentioning
confidence: 99%